HIJAB AND MUSLIM DRESS: YEDIDA KALFON STILLMAN'S PERSPECTIVE ON QUR'ANIC INTERPRETATION - Dzalfa Farida Humaira; Inayah Rohmaniyah (MIYAH: Jurnal Studi Islam, 2026)
This article examines Yedida Kalfon Stillman’s interpretation of Qur’anic verses as a basis for Muslim dress practices, with particular attention to the tradition of head covering (jilb?b). Drawing on her material culture approach, it highlights Stillman’s challenge to the notion of the jilb?b as an exclusive marker of Muslim female identity. Employing a qualitative library-based methodology, this study analyzes Stillman’s own publications as its primary sources alongside secondary scholarship on the jilb?b and women’s dress in Islam. To contextualize Stillman’s interpretive framework, the article adopts Karl Mannheim’s sociology of knowledge, exploring the relationship between her thought and the socio-historical realities that shaped her intellectual formation. Through a descriptive-analytical approach, the study identifies two major strands in Stillman’s interpretation: the broader normative prescriptions governing Muslim dress, and the emergence of sartorial distinctions imposed upon non-Muslims following the period of the Rightly Guided Caliphs. It argues that Stillman’s reading implicitly reflects a mun?sabah al-?y?t approach to Qur’anic interpretation, albeit articulated within a non-theological framework. This article contends that Stillman’s approach offers a productive contemporary framework for re-examining asb?b al-nuz?l, particularly through its integration of historical and ethnological analyses of clothing practices among the earliest Muslim communities.